Reversal and pinning of Curie point transformations in thin film piezoelectrics - PEROVA, TANIA (My University, 2011)
The Curie point for a rhombohedral piezoelectric thin film was established by in situ micro-Raman spectroscopy. The hysteresis in phase reversal and specific thermal conditions for disrupting such reversal were determined.
PUBLISHED
Keywords: Condensed matter physics; micro-Raman spectroscopy; Thin Films; Nanoscience & Materials